Lung mechanics and high-resolution computed tomography of the chest in very low birth weight premature infants - Mello, Rosane Reis de; Dutra, Maria Virgínia Peixoto; Ramos, José Roberto; Daltro, Pedro; Boechat, Márcia; Lopes, José Maria de Andrade; Lopes, José Maria de Andrade (São Paulo Medical Journal, 2003)
CONTEXT: Premature infant lung development may be affected by lung injuries during the first few weeks of life. Lung injuries have been associated with changes in lung mechanics. OBJECTIVE: To evaluate an association between lung mechanics and lung structural alterations in very low birth weight infants (birth weight less than 1500 g). DESIGN: A cross-sectional evaluation of pulmonary mechanics (lung compliance and lung resistance) and high resolution computed tomography of the chest at the time of discharge, in 86 very low birth weight infants born at Instituto Fernandes Figueira, a tertiary public healthcare institution in Rio de Janeiro, Brazil. Lung compliance and resistance were measured during quiet sleep. High resolution computed tomography was performed using Pro Speed-S equipment. MAIN MEASUREMENTS: Statistical analysis was performed by means of variance analysis (ANOVA/ Kruskal Wallis). The significance level was set at 0.05. RESULTS: Abnormal values for both lung compliance and lung resistance were found in 34 babies (43%), whereas 20 (23.3%) had normal values for both lung compliance and lung resistance. The mean lung compliance and lung resistance for the group were respectively 1.30 ml/cm H2O/kg and 63.7 cm H2O/l/s. Lung alterations were found via high-resolution computed tomography in 62 (72%) infants. Most infants showed more than one abnormality, and these were described as ground glass opacity, parenchymal bands, atelectasis and bubble/cyst. The mean compliance values for infants with normal (1.49 ml/cm H2O/kg) high resolution computed tomography, 1 or 2 abnormalities (1.31 ml/cm H2O/kg) and 3 or more abnormalities (1.16 ml/cm H2O/kg) were significantly different (p = 0.015). Our data were insufficient to find any association between lung resistance and the number of alterations via high-resolution computed tomography. CONCLUSION: The results show high prevalence of lung functional and tomographic abnormalities in asymptomatic very low birth weight infants at the time of discharge. They also show an association between lung morphological and functional abnormalities.